Evaluation of a toolkit for standardizing clinical measures of muscle tone. (8th August 2018) - McGibbon, Chris A; Sexton, Andrew; Hughes, Glen; Wilson, Adam; Jones, Melony; O'Connell, Colleen; Parker, Kim; Adans-Dester, Catherine; O'Brien, Anne; Bonato, Paolo
Abstract: Objective : To evaluate a new portable toolkit for quantifying upper and lower extremity muscle tone in patients with upper motor neuron syndrome (UMNS). Approach : Cross-sectional, multi-site, observational trial to test and validate a new technology. Setting : Neurorehabilitation clinics at tertiary care hospitals. Participants : Four cohorts UMNS patient, >6 mo post acquired brain injury, spinal cord injury, multiple sclerosis and cerebral palsy, and a sample of healthy age-matched adult controls. Measures : Strength: grip, elbow flexor and extensor, and knee extensor; range of motion (ROM): passive ROM (contracture) and passive-active ROM (paresis); objective spasticity: stretch-reflex test for elbow, and pendulum test for knee; subjective spasticity: modified Ashworth scale scores for elbow and knee flexors and extensors. Results : Measures were acquired for 103 patients from three rehabilitation clinics. Results for patient cohorts were consistent with the literature. Grip strength correlated significantly with elbow muscle strength and all patient populations were significantly weaker in upper- and lower-extremity compared to controls. Strength and paresis were correlated for elbow and knee but neither correlated with contracture. Elbow spasticity correlated with strength and paresis but not contracture. Knee spasticity correlated with strength, and subjective spasticity correlated with contracture. Significance : The BioTone ™ toolkit provided comprehensive objective measures for assessing muscle tone in patients with UMNS. The toolkit could be useful for standardizing outcomes measures in clinical trials and for routine practice.